Communicable Diseases Intelligence volume 4 issue 10 - 23 May 1980 - whole issue - No author listed (Communicable Diseases Intelligence, 1980)
Whole-issue pdf, comprising: Virus Reporting Scheme Article Salmonella typhimurium food-poisoning outbreaks [N.S.W.] Imported malaria. [Fairfield Hospital, Melbourne] Smallpox. [Brief report from WHO re recent notification and requirement of vaccination certificates] Australia - Communicable Diseases Intelligence Reporting Period - 01/05/1980 to 14/05/1980 Bulletin Number 80/10 Notifiable Diseases reported in Australia 4th 4 Weekly Period for 1980 22/03/1980 to 18/04/1980 inclusive